Industry Associations and Technology-based Growth in India. - Athreye, Suma; Chaturvedi, Sachin (European Journal of Development Research, 2007)
The study of industry associations occupies an uneasy ground in development economics. There is much empirical work that shows that industry associations fulfil important developmental roles in developing countries, often compensating for inadequacies in the business environment. Yet their status as institutions capable of generating growth is compromised because of the rent-seeking behaviour they embody. We study two different technology-based industries, namely software services and biotechnology, both of which formed industry associations to influence government policy and to aid the growth of their member firms, paying attention to their motivations for setting up, detailing the policies they sought to influence and their success as organisations.